Investigating ionisation and material ejection in ultraviolet matrix-assisted laser desorption\ionisation mass spectrometry imaging - Robinson, Kenneth Neil (2020)
Ultraviolet Matrix-Assisted Laser Desorption\Ionisation Mass Spectrometry (UV-MALDI MS) is a powerful analytical technique, allowing sensitive, unlabelled detection of a wide range of analytes. In recent decades this UV-MALDI has proven a highly successful Mass Spectrometry Imaging (MSI) modality, capable of imaging exogenous and endogenous compounds in complex biological tissues. Despite this, UV-MALDI MSI is hindered by incomplete knowledge regarding many aspects of desorption and ionisation. The researched presented in this thesis focuses on applying a quantitative metrological approach to investigate factors affecting desorption and ionisation in UV-MALDI MSI. The influence of analyte-to-matrix molar ratio and the use of the common additive trifluoroacetic acid (TFA) were explored for an array of matrices and analyte classes using multivariate analysis (MVA) techniques. A subset of these matrix-analyte systems was used to explore the relationship between ionisation, matrix optical absorption and laser fluence. UV-MALDI MSI laser sampling was investigated in detail us profilometry, quantifying material desorption and ion yield under MSI sampling conditions for the first time. Profilometry measurements were extended into tissue imaging, to probe the influence of tissue microenvironment on desorption and ionisation in a UV-MALDI imaging experiment. The first quantitative measurements of desorption, ion yield and ion suppression for MSI tissue data were achieved. MVA was used to identify probable causes of ion suppression, and to quantify tissue-region specific ion suppression, helping to inform and redefine data normalisation approaches.